Influence of knowledge, access to information, and health seeking behavior on antibiotic self-medication in Thailand - Darasawang, Worrayot; Laohasiriwong, Wongsa; Sornlom, Kittiphong; Mahato, Roshan Kumar (Intelektual Pustaka Media Utama, 2025)
Antibiotic self-medication (ASM) significantly contributes to antimicrobial resistance (AMR), a pressing global health concern. However, the impact of knowledge, health information access, and health-seeking behavior on ASM in Thailand is poorly understood. This study aimed to evaluate these influences using data from the 2021 health and welfare survey conducted by Thailand’s National Statistical Office. A generalized linear mixed model was applied to assess associations. Variables with a p-value <0.25 in bivariate analysis were further analyzed in a multivariable model, with adjusted odds ratios (AOR), 95% confidence intervals (CI), and p-values reported. Among 26,030 participants, 2.79% (95% CI: 2.59%-2.99%) engaged in ASM. Low knowledge of antibiotic use was strongly linked to ASM (AOR=4.30, 95% CI: 2.61-7.08), as was moderate knowledge (AOR=2.47, 95% CI: 1.49-4.09). Lack of antibiotic-related information significantly increased ASM (AOR=3.86, 95% CI: 3.03-4.92). Recent health-seeking behaviors, including over-the-counter medication (AOR=3.54, 95% CI: 2.02-6.21) and avoiding public and private hospitals, were also major contributors. Medication and transportation expenses were additional significant factors. Enhancing access to health information, knowledge, and healthcare services could reduce ASM in Thailand.